Implementasi Program CSR PT. Pertamina Hulu Rokan Kategori Pemberdayaan Ekonomi di Kelurahan Kampung Bandar Kota Pekanbaru - Aisyah Kusumo Dewi; Dadang Mashur (Penerbit Jurnal Indonesia, 2025)
Kampung Bandar Sub-district is one of the areas that has received a Corporate Social Responsibility (CSR) program from PT Pertamina Hulu Rokan, particularly in the category of community economic empowerment. The implementation of this program is based on the importance of CSR in improving community welfare through business capacity strengthening and local economic development in Kampung Bandar. The main problems faced in this area include limited market access, low technological literacy among business actors, and weak consistency of community participation after training activities are completed. Therefore, a more structured implementation strategy is required to ensure the program runs effectively and sustainably. This effort needs to be supported by competent human resources, effective communication among stakeholders, and continuous mentoring. The focus of this study is to describe the implementation of PT Pertamina Hulu Rokan’s CSR program in Kampung Bandar and to identify the obstacles encountered during its execution. The research employed a qualitative method with a descriptive approach. The analysis applied Van Meter and Van Horn’s implementation model, which emphasizes six main variables: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agents, disposition of implementers, and the socio-economic and political environment. The findings indicate that the CSR program has contributed positively to improving community skills and strengthening the local economy, although several challenges remain to be addressed.